ANALYSIS OF RISK FACTORS ATTENISTIC DERMATITIS ATTENDANCE ON THE CENTER IN PUSKESMAS PAUH PADANG - Sari, Dian; Rita, Nova (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
This study discusses the analysis of risk factors of atopic dermatitis occurrence in infants due to the high incidence rate of atopic dermatitis in infants. The purpose of this study was to determine what factors are at risk of incidence of atopic dermatitis in infants. This type of research is quantitative with case control study. The study was conducted from February to July 2017 with samples for 75 cases and control of 75 people (1: 1) so that the overall sample was 150 people. This research was conducted through interview using questionnaire. Result on Chi-Square was obtained p = 0.000 (p <0.05), where there was significant relationship between genetic, allergen, environment and hygiene with occurrence of atopic dermatitis in infants. Health workers can provide counseling to underfive mothers in Puskesmas Padang Puskesmas work area to be able to pay attention to food given to toddlers and to suppress incidence of atopic dermatitis in under fives. Health workers can increase the knowledge, awareness and willingness of the community about PHBS so as to reduce the incidence rate of atopic dermatitis. Maternal care in paying attention to the food in toddlers can reduce the incidence rate of atopic dermatitis in infants.